The epidemiology of pharmacologically treated attention deficit hyperactivity disorder (ADHD) in children, adolescents and adults in UK primary care - McCarthy Suzanne; Wilton Lynda; Murray Macey L; Hodgkins Paul; Asherson Philip; Wong Ian CK (BMC, 2012)
Abstract Background Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder characterised by the symptoms of inattention, impulsivity and hyperactivity. ADHD was once perceived as a condition of childhood only; however increasing evidence has highlighted the existence of ADHD in older adolescents and adults. Estimates for the prevalence of ADHD in adults range from 2.5-4%. Few data exist on the prescribing trends of the stimulants methylphenidate and dexamfetamine, and the non-stimulant atomoxetine in the UK. The aim of this study was to investigate the annual prevalence and incidence of pharmacologically treated ADHD in children, adolescents and adults in UK primary care. Methods The Health Improvement Network (THIN) database was used to identify all patients aged over 6 years with a diagnosis of ADHD/hyperkinetic disorder and a prescription for methylphenidate, dexamfetamine or atomoxetine from 2003-2008. Annual prevalence and incidence of pharmacologically treated ADHD were calculated by age category and sex. Results The source population comprised 3,529,615 patients (48.9% male). A total of 118,929 prescriptions were recorded for the 4,530 patients in the pharmacologically treated ADHD cohort during the 6-year study. Prevalence (per 1000 persons in the mid-year THIN population) increased within each age category from 2003 to 2008 [6-12 years: from 4.8 (95% CI: 4.5-5.1) to 9.2 (95% CI: 8.8-9.6); 13-17 years: from 3.6 (95% CI: 3.3-3.9) to 7.4 (95% CI: 7.0-7.8); 18-24 years: from 0.3 (95% CI: 0.2-0.3) to 1.1 (95% CI: 1.0-1.3); 25-45 years: from 0.02 (95% CI: 0.01-0.03) to 0.08 (95% CI: 0.06-0.10); >45 years: from 0.01 (95% CI: 0.00-0.01) to 0.02 (95% CI: 0.01-0.03). Whilst male patients aged 6-12 years had the highest prevalence; the relative increase in prescribing was higher amongst female patients of the same age - the increase in prevalence in females aged 6-12 years was 2.1 fold compared to an increase of 1.9 fold for their male counterparts. Prevalence of treated ADHD decreased with increasing age. Incidence (per 1000 persons at risk in the mid-year THIN population) was highest for children aged 6-12 years. Conclusions A trend of increasing prescribing prevalence of ADHD drug treatment was observed over the period 2003-2008. Prevalence of prescribing to adult patients increased; however the numbers treated are much lower than published estimates of the prevalence of ADHD. This study has added to the limited knowledge on ADHD prescribing in primary care, particularly in the area of drug treatment in adulthood.